lg | (x² - x - 1) / (x² + x - 2)| = 0
одз
модуль всегда не отрицателен, значит надо проверить чтобы знаменатель не равнялся 0
x² + x - 2 ≠0 D=1 + 8 = 9 x12 ≠ (-1+-3)/2 ≠ -2 1
и тело логарифма не равнялась 0
x² - x - 1 ≠ 0 D=1 + 4 = 5 x34=(1 +- √5)/2 ≠ (1+√5)/2 (1-√5)/2
===
| (x² - x - 1) / (x² + x - 2)| = 1
1. (x² - x - 1) / (x² + x - 2) = 1
x² - x - 1 = x² + x - 2
2x = 1
x = 1/2
2. (x² - x - 1) / (x² + x - 2) = -1
x² - x - 1 = -x² - x + 2
2x² - 2x - 3 = 0
D = 4 + 4*2*3 = 28
x23 = (2 +- √28)/4 = (1 +- √7)/2
ответ (1 +- √7)/2, 1/2
2 10\13-4\9*2 10\13+1\6*2 10\13=
1. 4\9*2 10\13=4\9*36\10=8\5
2. 1\6*2 10\13=1\6*36\10=6\10
3.2 10\13-8\5=36\13-8\5=180-104\65=76\65
4.76\65+6\10=152+78\130=230\130=1 10\13